Improving Students Activity and Students Learning Outcomes by Using Collaborations of RME (Realistic Mathematics Education) Dengan TGT (Team Games Tournament) - Abdul Jalal (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
The purpose of the research is to describe the students activities in using mix of RME (Realistic Mathematics Education) with TGT (Team Games Tournament) learning model. To describe the students learning outcomes in using mix of RME (Realistic Mathematics Education) with TGT (Team Games Tournament) learning model. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIIA at SMPI Al Barokah Banyuanyar. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: RME, TGT, students activity, and students learning outcomes